Pulmonary Involvement in Rheumatoid Arthritis - Zeynel Güldoğan,; Emel Ekşioğlu,; Hikmet Fırat,; Aytül Çakcı, (Archives of Rheumatology, 2007)
Objective: Pulmonary involvement is a frequent extraarticular finding in Rheumatoid arthritis (RA). Lungs of 81 RA patients were evaluated in this cross-sectional study. Patients and Methods: Symptoms, clinical and laboratory parameters, Ig levels, Health Assessment Questionnaire (HAQ), functional exercise level for daily living activities (six minute walk test), pulmonary function tests (PFT) and high resolution com puter tomography findings (HRCT) were investigated. Results: The HRCT and PFT was abnormal in 56.8% and 29.7% patients respectively. HRCT was abnormal in males, the elderly, late onset of the disease and in patients with a high erythrocyte sedimentation rate , C- reactive protein and Ig A levels. Coughing and sputum were frequent in HRCT abnormal patients. Statistical significance was found between HAQ and PFT and PFT and HRCT findings. No significant difference was found between the six minutes walk test and PFT and HRCT. Conclusion: Pulmonary involvement was more common with late onset of disease, and high Ig A levels but it did not decrease the functional exercise level for daily living activities. (Rheumatism 2007; 97-103)